Stochastic extension of cellular manufacturing systems: A queuing-based analysis - Fatemeh Fardis; Afagh Zandi; Vahidreza Ghezavati (Journal of Industrial Engineering International, 2013)
Clustering parts and machines into part families and machine cells is a major decision in the design of cellular manufacturing systems which is defined as cell formation. This paper presents a non-linear mixed integer programming model to design cellular manufacturing systems which assumes that the arrival rate of parts into cells and machine service rate are stochastic parameters and described by exponential distribution. Uncertain situations may create a queue behind each machine; therefore, we will consider the average waiting time of parts behind each machine in order to have an efficient system. The objective function will minimize summation of idleness cost of machines, sub-contracting cost for exceptional parts, non-utilizing machine cost, and holding cost of parts in the cells. Finally, the linearized model will be solved by the Cplex solver of GAMS, and sensitivity analysis will be performed to illustrate the effectiveness of the parameters.
Keywords: 650; Cellular manufacturing system; Stochastic arrival rate and service rate; Average waiting time; Queuing theory